Radio-synthesized protein-based nanoparticles for biomedical purposes - Varca, Gustavo H. C. (2014)
Protein-crosslinking whether done by enzymatic or chemically induced pathways increases the overall stability of proteins. In the continuous search for alternative routes for protein stabilization we report a novel technique - radio-induced synthesis of protein nanoparticles - to achieve size controlled particles with preserved bioactivity. Papain was used as model enzyme and the samples were irradiated at 10. kGy in a gammacell irradiator in phosphate buffer (pH=7.0) and additives such as ethanol (0-40%) and sodium chloride (0-25%). The structural rearrangement caused by irradiation under defined conditions led to an increase in papain particle size as a function of the additive and its concentration. These changes occur due to intermolecular bindings, of covalent nature, possibly involving the aromatic amino acids. Ethanol held major effects over papain particle size and particle size distribution if compared to sodium chloride. The particles presented relative retained bioactivity and the physic-chemical characterization revealed similar fluorescence spectra indicating preserved conformation. Differences in fluorescence units were observed according to the additive and its concentration, as a result of protein content changes. Therefore, under optimized conditions, the developed technique may be applied for enzyme nanoparticles formation of controllable size and preserved bioactivity.